Planning milking facilities for dairy expansion - Smith, John F., 1962- (Kansas Agricultural Experiment Station, 2011)
Construction of a new milking center or remodeling existing milking parlors is a very important decision that can dramatically affect the labor efficiency and profitability of a dairy. Dairy producers should set reasonable goals for present and future needs. All options and configurations of the milking center should be considered and evaluated on a 15-yr planning horizon. Milking parlors should be designed to allow use of a full milking hygiene and add flexibility in management of the parlor.
Keywords: Expansion; Milking facilities; Construction